Pendampingan Pembuatan Tempat Pensil Kreatif dari Botol dan Sedotan Bekas - Naura Yuiza Rahayu; Siti Nortasya; Istiyati Mahmudah (Lembag, 2025)
The purpose of this community service activity is to assist Madrasah Ibtidaiyah students in creating pencil holders using used bottles and straws. This is a project-based learning activity that instills values of creativity and environmental awareness. The activity is part of the implementation of the Merdeka Curriculum, which emphasizes contextual learning and skills relevant to the modern era.By participating as facilitators, PGMI students gain firsthand experience in designing and implementing project-based learning. The activity includes providing materials, demonstrations, hands-on practice, and evaluation of results. The outcomes show an increase in students' creativity and awareness of the importance of transforming recycled materials into useful products for the environment. Moreover, this activity provides valuable experience for PGMI students, helping them learn to apply active and practical learning approaches.